Asuhan Kebidanan Komprehensif Ny. A Umur 30 Tahun Grandemulti dengan Anemia di Rumah Sakit Umum Daerah Bumiayu Tahun 2024 - Nunung Febriyaningsih; Endang Susilowati; Nurhidayah Nurhidayah (NAJ Nursing Applied Journal, 2025)
The maternal mortality rate is an indicator of health status and is one of the health problems in the world. Brebes Regency is one of the contributors to the highest maternal mortality rate in Central Java. In 2021, the Bumiayu Regional General Hospital contributed to the Maternal Mortality Rate in Brebes Regency by 15 cases. The purpose of this research is to be able to provide comprehensive midwifery care for Mrs. The research method used is qualitative descriptive research with a case study approach. The case study carried out is in the form of comprehensive midwifery care that examines pregnancy, childbirth, newborns, postpartum and family planning with Varney's 7-step midwifery management and SOAP. The results of the pregnancy were found to be anemia and CED, delivery by caesarean section, the newborn was normal, during the neonatal period physiological jaundice was found, then appropriate management was carried out so that it could be resolved, during the postpartum period no problems were found, the mother used MOW KB. The conclusion obtained was that care had been carried out in accordance with midwifery service standards and the problem of anemia and CED had not been resolved